2019
DOI: 10.1007/s10107-019-01402-2
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial n-fold integer programming and applications

Abstract: Many fundamental NP-hard problems can be formulated as integer linear programs (ILPs). A famous algorithm by Lenstra solves ILPs in time that is exponential only in the dimension of the program, and polynomial in the size of the ILP. That algorithm became a ubiquitous tool in the design of fixedparameter algorithms for NP-hard problems, where one wishes to isolate the hardness of a problem by some parameter. However, in many cases using Lenstra's algorithm has two drawbacks: First, the run time of the resultin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 57 publications
2
50
0
Order By: Relevance
“…, n} : x i = 0} denote the support of x. The main purpose of this paper is to establish lower and and upper bounds on the minimal size of support of an optimal solution to Problem (1) which are polynomial in m and the largest binary encoding length of an entry of A. Polynomial support bounds for integer programming [5,1] have been successfully used in many areas such as in logic and complexity, see [14,12] in the design of efficient polynomial-time approximation schemes [10,11], in fixed parameter tractability [13,16] and they were an ingredient in the solution of cutting stock with a fixed number of item types [8]. These previous bounds however were tailored for the integer feasibility problem only and thus depend on the largest encoding length of a component of the objective function vector if applied to the optimization problem (1).…”
Section: Introductionmentioning
confidence: 99%
“…, n} : x i = 0} denote the support of x. The main purpose of this paper is to establish lower and and upper bounds on the minimal size of support of an optimal solution to Problem (1) which are polynomial in m and the largest binary encoding length of an entry of A. Polynomial support bounds for integer programming [5,1] have been successfully used in many areas such as in logic and complexity, see [14,12] in the design of efficient polynomial-time approximation schemes [10,11], in fixed parameter tractability [13,16] and they were an ingredient in the solution of cutting stock with a fixed number of item types [8]. These previous bounds however were tailored for the integer feasibility problem only and thus depend on the largest encoding length of a component of the objective function vector if applied to the optimization problem (1).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the prototypical uses of Lenstra's algorithm lead to FPT algorithms which have a double-exponential (i.e., 2 2 k O (1) ) dependency on the parameter, such as the algorithms for Closest String [15] or Swap Bribery [8]. Very recently, Knop et al [22] showed that many of these ILP formulations have a particular format which is solvable exponentially faster than by Lenstra's algorithm, thus bringing down the dependency on the parameter down to single-exponential. This leads us to wonder what is the true complexity of, e.g., Resiliency Closest String?…”
Section: Discussion and Open Problemsmentioning
confidence: 99%
“…In spite of this restrictive structure, n-fold integer programming found a number of applications, e.g., in scheduling [34] and voting [38]. See also the works of Dvorák et al [15] and Knop et al [35] for very recent generalizations and extensions of the this technique. It is quite non-obvious how the technique of n-fold integer programming compares to ours.…”
Section: Integer Linear Programmingmentioning
confidence: 99%